2015
DOI: 10.1093/ntr/ntv231
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Withdrawal Amongst African American, Hispanic, and White Smokers

Abstract: The current study provides some initial evidence that there may be qualitative differences in the types of tobacco withdrawal symptoms experienced among non-Hispanic African American, Hispanic, and non-Hispanic white smokers. Extending this line of inquiry may elucidate mechanisms involved in tobacco-related health disparities and ultimately aid in reducing the public health burden of smoking in racial/ethnic minority populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…The gender difference observed here is consistent with prior studies of NW (Leventhal et al, 2007; Xu et al, 2008; Cosgrove et al, 2012; Hogle and Curtin, 2006). The literature on racial and ethnic variation in NW is equivocal, with some studies of African American smokers reporting more severe NW (Bello et al, 2015) and others reporting less severity (Riedel et al, 2003; Robinson et al, 2014). That African American participants in the current study were less likely to be offered NRT upon hospital admission may account for the observed effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender difference observed here is consistent with prior studies of NW (Leventhal et al, 2007; Xu et al, 2008; Cosgrove et al, 2012; Hogle and Curtin, 2006). The literature on racial and ethnic variation in NW is equivocal, with some studies of African American smokers reporting more severe NW (Bello et al, 2015) and others reporting less severity (Riedel et al, 2003; Robinson et al, 2014). That African American participants in the current study were less likely to be offered NRT upon hospital admission may account for the observed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Preexisting psychiatric conditions (Pomerleau et al, 2000; Xian et al, 2005); exposure to trauma (Dedert et al, 2012); alcohol and other drug use (Weinberger et al, 2010); female gender (Xu et al, 2008); African American ethnicity (Bello et al, 2015); and genetic vulnerability (Xian et al, 2003; Lazary et al, 2014) have been linked with greater intensity of NW. That individuals experience and present with NW in different forms is of interest clinically and perhaps particularly so in an environment in which the cues to smoke have been removed, as is the case for hospitals with complete smoking bans.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is more frequent in minority populations (e.g., racial and sexual minorities) and in those who have low levels of education and SES (Antin, Lipperman-Kreda, & Hunt, 2015; Hiscock, Bauld, Amos, Fidler, & Munafo, 2012; Leventhal, 2016; Siahpush, Singh, Jones, & Timsina, 2010; USDHHS, 2014). These same groups also struggle disproportionately with smoking cessation and suffer increased nicotine withdrawal symptoms (Bello et al, 2016; Croghan et al, 2010). Low SES individuals are less likely to try to quit smoking (Reid, Hammond, Boudreau, Fong, & Siahpush, 2010) and when they do make a quit attempt, they are less likely to succeed (Gilman, Abrams, & Buka, 2003; Reid et al, 2010).…”
Section: Applying Social Context To Smokingmentioning
confidence: 99%
“…Although cigarette consumption rates were consistently found to be much higher among non-Hispanic Whites and other racial/ethnic groups (vs. African Americans; Trinidad et al, 2015; Evans-Polce, Vasilenko, & Lanza, 2015; Jamal et al, 2014; Herzog & Pokhrel, 2012), African American smokers are more susceptible to the effects of smoking on tobacco-related disease morbidity and mortality (American Cancer Society, 2016; DeLancey, Thun, Jemal, & Ward, 2008; Haiman et al, 2006; Irvin Vidrine, Reitzel, & Wetter, 2009), are less likely than other racial groups to initiate a quit attempt (Bacio, Guzman, Shapiro, & Ray, 2014; Fu et al, 2008; Hahn, Folsom, Sprafka, & Norsted, 1990; Trinidad, Perez-Stable, White, Emery, & Messer, 2011), appear to be at greater risk of relapse following a cessation attempt (Choi, Okuyemi, Kaur, & Ahluwalia, 2004), and may experience more extensive affective disturbances during acute abstinence (Bello et al, 2016). Moreover, recent literature has illustrated disproportionately higher rates of menthol cigarette smoking among African Americans, with African American menthol smokers being more likely to initiate smoking and less likely to successfully quit smoking than non-Hispanic White non-menthol smokers, despite showing more motivation to quit smoking (Alexander et al, 2016; Keeler et al, 2016; Stahre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%